1989
DOI: 10.1111/j.1476-5381.1989.tb11920.x
|View full text |Cite
|
Sign up to set email alerts
|

The properties of 5‐HT3 receptors in clonal cell lines studied by patch‐clamp techniques

Abstract: 1 The characteristics of transmembrane currents evoked by 5-hydroxytryptamine (5-HT) in the neuroblastoma x Chinese hamster brain cell line On outside-out membrane patches excised from both NCB-20 and NlE-115 cells, 5-HT induced small inward currents which could not be clearly resolved into discrete single channel events. Such responses were: (i) reversibly antagonized by GR 38032F (1 nM) (ii) reversed in sign at 0 mV, and (iii) subject to desensitization. 6 Fluctuation analysis of inward currents evoked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 45 publications
8
79
0
Order By: Relevance
“…Electrophysiological data support the suggestion that the charged groups line portals within the sides of the ICD, and influence the ion flux between the cytoplasm and the inner vestibule at the base of the pore (Miyazawa et al 1999 ;Unwin, 2000). As the widest region of the portals resembles the diameter of a hydrated permeant ion, they provide an explanation for the homomeric 5-HT 3 channel having a much smaller unitary conductance than most nAChRs, despite their similar ionic permeabilities and very similar M2 sequences (Brown et al 1998 ;Lambert et al 1989 ;Malone et al 1991 ;Mochizuki et al 2000 ;Yakel et al 1990 ;Yang, 1990). Additional studies have shown that the conductance of the channel can be dynamically altered by sulphydryl modifying reagents (Deeb et al 2007) and the permeability of divalent cations is also altered by mutations in this region (Livesey et al 2008).…”
Section: Channel Conductancementioning
confidence: 99%
“…Electrophysiological data support the suggestion that the charged groups line portals within the sides of the ICD, and influence the ion flux between the cytoplasm and the inner vestibule at the base of the pore (Miyazawa et al 1999 ;Unwin, 2000). As the widest region of the portals resembles the diameter of a hydrated permeant ion, they provide an explanation for the homomeric 5-HT 3 channel having a much smaller unitary conductance than most nAChRs, despite their similar ionic permeabilities and very similar M2 sequences (Brown et al 1998 ;Lambert et al 1989 ;Malone et al 1991 ;Mochizuki et al 2000 ;Yakel et al 1990 ;Yang, 1990). Additional studies have shown that the conductance of the channel can be dynamically altered by sulphydryl modifying reagents (Deeb et al 2007) and the permeability of divalent cations is also altered by mutations in this region (Livesey et al 2008).…”
Section: Channel Conductancementioning
confidence: 99%
“…Lambert et al 18) reported that application of 5-HT to NCB-20 cells produced ion current exclusively via 5-HT 3 receptor activation. This conclusion was based on the potent blockade of the response observed with GR 38032F and ICS 205-930, the 5-HT 3 receptor antagonists.…”
Section: Effect Of Proanthocyanidin On 5-ht-induced Currentsmentioning
confidence: 99%
“…This conclusion was based on the potent blockade of the response observed with GR 38032F and ICS 205-930, the 5-HT 3 receptor antagonists. 18) In our study, we firstly determined the concentration-response relationship for the effects of 5-HT on 5-HT 3 receptor-mediated currents. The application of 0.1-300 mM 5-HT for 5 s at 2 min intervals to NCB-20 cells caused a concentration-dependent inward current at Ϫ50 mV, and 30 mM 5-HT induced a near-maximal response.…”
Section: Effect Of Proanthocyanidin On 5-ht-induced Currentsmentioning
confidence: 99%
“…In mouse NIE-115 neuroblastoma cells, 5-HT3 receptors have been investigated in detail. From these cells the functional characteristics of the 5-HT3 receptor-mediated macroscopic whole-cell ion current (Neijt et al, 1986;Lambert et al, 1989) and microscopic single channel events Hooft & Vijverberg, 1995), as well as the ligand-binding profile of the recognition site (Hoyer & Neijt, 1988;Lummis et al, 1990) and the primary sequence of the cloned 5-HT3 receptor subunit (5-HT3R-A) and a splice variant (5-HT3R-A,) have been reported (Hope et al, 1993).…”
Section: Introductionmentioning
confidence: 99%